The disappearance of relict permafrost in boreal north America: Effects on peatland carbon storage and fluxes - M. R. TURETSKY; R. K. WIEDER; D. H. VITT; R. J. EVANS; K. D. SCOTT (Global Change Biology, 2007)
Boreal peatlands in Canada have harbored relict permafrost since the Little Ice Age due to the strong insulating properties of peat. Ongoing climate change has triggered widespread degradation of localized permafrost in peatlands across continental Canada. Here, we explore the influence of differing permafrost regimes (bogs with no surface permafrost, localized permafrost features with surface permafrost, and internal lawns representing areas of permafrost degradation) on rates of peat accumulation at the southernmost limit of permafrost in continental Canada. Net organic matter accumulation generally was greater in unfrozen bogs and internal lawns than in the permafrost landforms, suggesting that surface permafrost inhibits peat accumulation and that degradation of surface permafrost stimulates net carbon storage in peatlands. To determine whether differences in substrate quality across permafrost regimes control trace gas emissions to the atmosphere, we used a reciprocal transplant study to experimentally evaluate environmental versus substrate controls on carbon emissions from bog, internal lawn, and permafrost peat. Emissions of CO 2 were highest from peat incubated in the localized permafrost feature, suggesting that slow organic matter accumulation rates are due, at least in part, to rapid decomposition in surface permafrost peat. Emissions of CH 4 were greatest from peat incubated in the internal lawn, regardless of peat type. Localized permafrost features in peatlands represent relict surface permafrost in disequilibrium with the current climate of boreal North America, and therefore are extremely sensitive to ongoing and future climate change. Our results suggest that the loss of surface permafrost in peatlands increases net carbon storage as peat, though in terms of radiative forcing, increased CH 4 emissions to the atmosphere will partially or even completely offset this enhanced peatland carbon sink for at least 70 years following permafrost degradation.